A storytelling exercise or a Library activity with a correction component - Chijova M. S., Kukushkina E. V. (Pedagogical excellence and pedagogical technologies, 2018)
the article reveals the methods of preparing and conducting classes on telling fairy tales to children of five to seven years with ASD, visiting the Federal Resource Center for Organization of Comprehensive Support to Children with Autism Spectrum Disorders: principles of literary material selection, work with the text, preparation of demonstration material. The content of the lesson is aimed at developing the child's mental functions, expanding his ideas about the world around him.
Keywords: социальная адаптация; конструирование; Social Adaptation; РАС; construction; кумулятивная сказка; сенсорная интеграция; три зоны; ASD; cumulative tale; sensored integration; three zones